Identification of Captured Rat Species and Detection of Leptospira Bacteria: Study at the Gapura Surya Nusantara Passenger Terminal, Tanjung Perak Port, Surabaya - Mas Adhi Hardian Utama; Suhartono Suhartono; Budiyono Budiyono (Majalah Kesehatan Indonesia, 2023)
Leptospirosis is transmitted through water or food contaminated by the urine of infected animals, with rats as the potential main reservoir. This research aims to describe the species and gender and analyze the presence of Leptospira bacteria in rats at the Terminal Gapura Surya Nusantara (GSN) Port in Tanjung Perak, Surabaya. This study employed a descriptive cross-sectional design. Samples were captured using traps baited with salted fish. The captured rat kidneys were tested using Real-Time Polymerase Chain Reaction (RT-PCR) at the Vector and Disease Carrier Animal Laboratory Installation of the Center for Environmental Health and Disease Control Technology (BBTKLPP) in Surabaya. Data were analyzed using frequency distribution tables. The research results indicate Rattus norvegicus as the most dominant species, followed by Mus musculus and Rattus tanezumi. Out of a total of 19 captured rats, 89.5% were male, and 10.5% were female. RT-PCR testing for Leptospira bacteria in rat kidneys showed that only 3 rats (15.8%) tested positive, while 16 rats (84.2%) tested negative. Interestingly, rats identified as exposed to Leptospira bacteria were only found in the Rattus norvegicus species and were male. This highlights the potential role of species and gender in the spread of these bacteria. Increased surveillance and control measures are needed to address the issue of rats and the spread of Leptospira bacteria. The Rattus norvegicus species, particularly the males exposed to Leptospira bacteria, requires special attention. Abstrak: Leptospirosis ditularkan melalui air atau makanan terkontaminasi oleh urine hewan terinfeksi, dengan tikus sebagai potensi reservoir utama. Penelitian ini bertujuan untuk mendeskripsikan spesies dan jenis kelamin, serta menganalisis keberadaan bakteri Leptospira pada tikus di Terminal Gapura Surya Nusantara (GSN) Pelabuhan Tanjung Perak Surabaya. Penelitian ini adalah deskriptif cross-sectional. Sampel diambil dengan perangkap menggunakan umpan ikan asin. Ginjal tikus yang tertangkap diuji menggunakan metode Real Time Polymerase Chain Reaction (RT-PCR) di Instalasi Laboratorium Vektor dan Binatang Pembawa Penyakit Balai Besar Teknik Kesehatan Lingkungan dan Pengendalian Penyakit (BBTKLPP)  Surabaya. Data dianalisis menggunakan tabel distribusi frekuensi. Hasil penelitian menunjukkan Rattus norvegicus sebagai spesies paling dominan, diikuti oleh Mus musculus dan Rattus tanezumi. Dari total 19 tikus yang berhasil ditangkap, sebanyak 89,5% adalah jantan dan 10,5% betina. Hasil uji RT-PCR untuk bakteri Leptospira pada ginjal tikus menunjukkan hanya 3 tikus (15,8%) positif, sedangkan 16 tikus (84,2%) negatif. Menariknya, tikus yang teridentifikasi terpapar oleh bakteri Leptospira hanya ditemukan pada jenis Rattus norvegicus dan berjenis kelamin jantan. Hal ini menyoroti peran potensial spesies dan jenis kelamin dalam penyebaran bakteri tersebut. Peningkatan pengawasan dan pengendalian dibutuhkan untuk menanggulangi masalah tikus dan penyebaran bakteri Leptospira. Spesies Rattus norvegicus yang berjenis kelamin jantan, sebagai tikus yang terpapar bakteri Leptospira, memerlukan perhatian khusus.